Improvement of orbit determination using laser altimeter crossovers: JUICE mission case study. (May 2021) - Villamil, S.; Dirkx, D.; Stark, A.; Hussmann, H.
Abstract: This work evaluates the added benefit of using laser altimeter measurements for orbit reconstruction. As a spacecraft orbits a celestial body, its altimetry swaths progressively cross previous swaths. These locations, known as crossover points, yield valuable information about the orbited body and the spacecraft trajectory. The mathematical expressions for the inclusion of crossover measurements into orbit determination algorithms are presented and evaluated. It is shown that a first-order approximation of these expressions is insufficient and a more detailed expression is developed. To evaluate the impact of altimetry crossover measurements on orbit determination, the planetary mission Jupiter Icy moons Explorer (JUICE) by the European Space Agency (ESA) is used as a case study by means of a covariance analysis. In this initial analysis, the assumption is made that all altimetry measurements are obtained with nadir pointing which limits the direct applicability of our method until pointing is accounted for. Highlights: Altitude difference crossover measurements improve orbit determination. Crossovers reduce position uncertainty marginally due to Doppler precision advancements. Laser altimetry crossovers with JUICE mission as case study. Covariance analysis of estimation uncertainty when altimetry crossovers are included.